Streamlining Induced Pluripotent Stem Cell Biomanufacturing: Gene Editing, Bio-Antibiotics, and 3D Culture Systems for Regenerative Medicine - Wang, Mianjun (My University, 2024)
Stem cell therapy, as one of regenerative medicines, has been shown to be a promising treatment for chronic and degenerative diseases. However, the large-scale production of therapeutic stem cells faces major difficulties including the high costs, the contamination possibilities and the stringent sterilization requirements. This study aims to address these problems by developing a novel sterilization-free bioreactor designed for the efficient production of iPSCs, which are derived from adult cells and minimize the ethical issues, holding the potential for more accessible stem cell therapy and personalized medicine. A major goal of this research is to streamline the iPSCs manufacturing process while ensuring cell quality and decreasing the costs for it. To achieve this, three key innovations were applied to the sterilization-free bioreactor system: (1) different gene editing techniques were performed to knock out the Beta-2-microglobulin (B2M) gene in iPSCs, reducing immune recognition and enhancing their potential for therapeutic applications; (2) human antimicrobial peptides were introduced to prevent contamination, further enhancing the bioreactor’s suitability for therapeutic use; and (3) a novel 3D cell culture method was developed to interact with cells in 3D culture. Results demonstrated that CRISPR/Cas9 demonstrated high efficiency and cell viability, while Fanzor’s performance improved significantly when combined with caspase inhibitors. Second, different human-derived antimicrobial peptides were introduced to prevent bacterial contamination, offering an effective and safe alternative to conventional antibiotics. Third, a novel 3D cell culture system using Microlinkers coated with E-cadherin showed cell-cell interactions and impacted cell behaviors. These findings highlight the potential of a sterilization-free bioreactor for scalable and cost-effective iPSCs production. By improving efficiency, safety, and cell quality, this study provides the feasibility of stem cell therapies and a solid foundation for regenerative treatments for patients.
Keywords: Stem Cell; Gene Editing; Cell Culture